Standard details for fire-resistive building construction - Przetak, Louis (New York : McGraw Hill Education, 1977)
The purpose of this book is to provide graphic illustrations of the various methods or assemblies for achieving fire resistance of structural parts, walls, partitions, floors, and roofs for the various time periods of 1,2,3, and 4 hours as listed in the 1973 and 1976 editions of the uniform building code, chapter 43.
Preface -- Abbreviations -- Acknowledgments -- Introduction -- Section S. Structural parts -- Section W. Walls and partitions -- Section F. Floors and roofs -- Section HT. Heavy Timber -- Appendix -- Indexes.
Includes index.
Keywords: BUILDING, FIREPROOF